TOTAL COLONY CHARACTERIZATION OF AEROBIC BACTERIA OF THE ORAL CAVITY ON PEATLANDS WATER AND PDAM WATER - Senggara, Bayu Yordha; Tri Putri, Deby Kania; Aspriyanto, Didit (Dentino, 2018)
Background: South Kalimantan peatland water is approximately 8000 km2. Barito Kuala has 40,858 hectares or 90% of the area classified as peatland water. Society uses peatlands water with acidic pH(3.5-4.5) for everyday purposes including rinsing and brushing teeth. The acidic nature of peatland water can affect the growth of bacterial colonies in the oral cavity so that the acidic conditions of the oral cavity increases and the effect on the occurrence of dental caries. In addition PDAM water is water from river water that is processed through several stages to become clean water after filtration and disinfection stages to eliminate microorganisms. Objective: this study aims to determine the characterization of the number of colonies of aerobic bacteria of the oral cavity on peatland water and PDAM water. Methods: This study used quasi experimental method with post test only control group design. The study sample consisted of 30 respondents. Research materials were 4ml of a result of the salivary gargle on peatland water and PDAM water then the number of aerobic bacteria colonies were calculated by the method of TPC (Total Plate Count) and characterization of aerobic bacteria was done by using catalase test, test MSA and coagulase test. Results: This study showed that there were 1653 CFU/ml of aerobic aerobic colony, whereas in water of PDAM there were 1264 CFU/ml of aerobic colonies. In the characterization tests of aerobic bacteria colonies showed that there were Staphylococcus aureus and Staphylococcus epidermidis bacteria on gargle water of peatland or PDAM water. Independent t-test results showed significant differences in aerobic bacterial colonies in peatland water and PDAM water (p = 0.001)(p = 0.002)(p <0.05). Conclusion: Based on this study it can be concluded that the number of Staphylococcus aureus and Staphylococcus epidermidis found in the oral cavity of children saliva who gargled with peatland water are higher than the number of Stapylococcus aureus and Staphylococcus epidermidis found in the saliva of children who gargle with PDAM water.